Optimization Of Isolation Method Of Carrageenan From Kappaphycuss Alvarezii Doty Using Factorial Experimental Design - Ketut Widyani Astuti; Ni Putu Ayu Dewi Wijayanti; I Gusti Ngurah Agung Dewantara Putra; Ni Putu Linda Laksmiani (Institute for Research and Community Services Udayana University, 2017)
Kappaphycus alvarezii Doty is a species of red algae ( Rhodophyceae) producing kappa carrageenan. The value of carrageenan will increase if it is able to form thermoreversible gels. The quality of carrageenan is determined by the isolation method which includes several stages, namely soaking, extraction, purification, and drying. This study aims to obtain an optimum isolation method of carrageenan from seaweed Kappaphycus alvarezii Doty using the factorial experimental design software, Design Expert Version.7.0.0. with the characteristics that meet the standards set by FAO. The seaweed was collected from the sea in Nusa Lembongan, Bali Province. The carrageenan isolation method was optimized by varying three factors, namely the concentration of NaOH (4% and 8%), extraction time (0.5 hour and 3 hours), and precipitation time (0.25 hour and 0.5 hour) in order to obtain 8 formulae which then went through an evaluation of the physical and chemical characteristics of the carrageenan. The physical and chemical characteristics include the yield, viscosity, sulfate content, and ash content, analyzed using Design Expert Version 7.0.0 program to determine the optimum method of isolation. The analysis showed that the optimum method of carrageenan isolation was using NaOH with a concentration of 4.40%, the extraction time of 2.16 hours and the precipitation time of 0.29 hour. The physical and chemical characteristics of carrageenan with the optimum isolation method include the yield of 25.73%, the viscosity of 11.92 cPs, sulfate content of 31.95% and the ash content of 26.16% which have met the standards set by FAO.